Two new species of the marine isopod genus Cirolana Leach, 1818 (Crustacea: Isopoda: Cirolanidae) from the coast of the western Gulf of Thailand - Rodcharoen, Eknarin; Bruce, Niel L. (Zootaxa, 2021)
Cirolana khamensis sp. nov. and C. parawongat sp. nov. are described from specimens collected in the western Gulf of Thailand at depths of 8 metres and 1 metre, respectively. Both species belong to the Cirolana ‘pleonastica-group’ with tubercles on the dorsal surfaces, transverse sutures on the pereonites, pleonite 3 not posteriorly produced and pleonite 4 posterolaeral margin rounded. Cirolana khamensis sp. nov. can be distinguished from other species of Cirolana ‘pleonastica-group’ by lateral margin of uropodal exopod having five robust seatae and a continuous row of plumose marginal setae, pereonites 1–3 each with a single transverse impressed line; antennula peduncle with articles 1 and 2 distinct and articulated peduncle; pleotelson dorsal surface with two sub-median longitudinal carinae, each of which has four prominent tubercles. Cirolana parawongat sp. nov. can be distinguished by pereonites 1–3 without a single transverse impressed line and having nine tubercles on pleonite 4 and 5. A dichotomous key to Cirolana ‘pleonastica-group’ in South-East Asia region is given.